A “Mestres do Terror”: mulheres, gênero e quadrinhos na década de 1980 - Peplow, Willian Fernando (2020)
This dissertation aims to analyze how women were represented in the stories published in the comic Masters of Terror, during the 1980s. In this sense, we problematized the insertion of comics in Brazil and the emergence of the horror genre in this editorial segment. We reflected on the moment of construction of the sources used in this study, Brazil in the 1980s, observing political, economic and cultural aspects. We also question the production of HQ Masters of Terror, the rofessionals involved in its construction, the aesthetics and structure of the magazine. To better understand the representations about women and femininity (s), we also discussed the nuances with the representations about men and masculinity (s) present in the stories of this journal. We used as a source 51 editions of the Masters of Terror comic published during the 1980s. The theoretical basis of the research comes from discussions of Cultural History, from the category of gender analysis by Joan Scott and the concept of Practices and Representations by Roger Chartier.